2019
DOI: 10.1155/2019/6384360
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the High-Temperature and Low-Temperature Performance of Polyphosphoric Acid/Styrene-Butadiene-Styrene Composite-Modified Asphalt

Abstract: The high-performance asphalt materials are used to replace the ordinary road asphalt that cannot meet the requirements of natural environment and traffic situation, which is the effective way to solve poor asphalt pavement durability. In this paper, polyphosphoric acid- (PPA-) modified asphalt and polyphosphoric acid (PPA)/styrene-butadiene-styrene (SBS) composite-modified asphalt with different PPA content were prepared by using two-type asphalt. The effect of PPA modifier on asphalt was analyzed by using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The high-speed shear instrument model FM300 produced by Shanghai Fluke Liquid Machinery Manufacturing Company was used in this study. Amounts of 5%, 10%, and 15% of the seashell powder modifier were added to the asphalt by mass ratio following methods in the literature [17,45]. The test sample preparation process is as follows: an oven is used to maintain the temperature at 135 • C in order to heat the base asphalt for 1 h; it is poured into the container, and an electric furnace (150 ± 5 • C) is immediately used to heat it; it is then mixed with the seashell powder modifier, and this mixture is manually stirred for 10 min; the high-speed shear is used to stir at 2000 r/min for 10 min; finally, stirring is carried out at 3000 r/min for 30 min.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The high-speed shear instrument model FM300 produced by Shanghai Fluke Liquid Machinery Manufacturing Company was used in this study. Amounts of 5%, 10%, and 15% of the seashell powder modifier were added to the asphalt by mass ratio following methods in the literature [17,45]. The test sample preparation process is as follows: an oven is used to maintain the temperature at 135 • C in order to heat the base asphalt for 1 h; it is poured into the container, and an electric furnace (150 ± 5 • C) is immediately used to heat it; it is then mixed with the seashell powder modifier, and this mixture is manually stirred for 10 min; the high-speed shear is used to stir at 2000 r/min for 10 min; finally, stirring is carried out at 3000 r/min for 30 min.…”
Section: Sample Preparationmentioning
confidence: 99%
“…A high-speed shear mixer rated at 300 W and manufactured by Shanghai Frank (Shanghai, China) was used in the sample preparation to maximize the mixing consistency. Based on previous study and test experience [19,[49][50][51][52][53], the proportion of ES in the asphalt was 5, 10, and 15% (mass percentage), and the shear rate was optimized. The sample preparation process was as follows.…”
Section: Flash Point (°C)mentioning
confidence: 99%
“…Flexible pavement performance can be enhanced through change in aggregate gradation and/or source [3,4], modification of binder through polymers [5], styrene-butadiene-styrene (SBS) [6,7], crumb rubber [8,9], Elvaloy [10], polyethylene [11][12][13], lime [14][15][16][17], and costly nanomaterials [18,19]. Poly phosphoric acid (PPA) has been extensively used as bitumen modifier and has been reported to improve highand intermediate-temperature performance of asphalt [20]. Studies conducted on nanomaterials, such as nano-TiO 2 , nano-SiO 2 , and nano-ZnO, have shown that bitumen modified with nanoparticles results in significant improvement in high-temperature performance of asphalt [21,22], but it is considered as an expansive solution.…”
Section: Introductionmentioning
confidence: 99%